Modern Horizons of Evolution: From Nature, a Human Being and Technology to Technogenic Man-Measurable System - Evgeny KAMENSKY; Irina ASEEVA; Vicktoria BELKINA (Communications of International Proceedings, 2020)
Nowadays the issues of understanding the technogenic elements of environmental structure of human life and activities in the framework of socio-humanitarian knowledge are beyond the focus of scientific research. The article presents author’s understanding of the phenomenon, which we define as Technogenic Man-Measurable Systems (TMMS) in its most futurological aspect, reflecting, however, the existing trends in the development of scientific and technological progress.
Keywords: Technogenic Man-Measurable Systems (TMMS); Technosphere; Anthropic principle; Hybridization; Synergetics.